41 Sentinel node mapping vs. lymphadenectomy in endometrial cancer: a systematic review and meta-analysis. (18th September 2019) - Bogani, G; Ditto, A; Murgia, F; Chiappa, V; Leone, U; Raspagliesi, F
Abstract : Objectives: Sentinel node mapping is increasingly being utilized for endometrial cancer staging. However, only limited evidence supporting the adoption of sentinel node mapping instead of conventional lymphadenectomy is still available. Here, we aimed to review the current evidence comparing sentinel node mapping and lymphadenectomy in endometrial cancer staging. Methods: This systematic review was registered in the International Prospective Register of Systematic Reviews. Der-Simonian and Laird random-effects models were used to pool log transformed event rates and estimated 95%CI for dichotomous outcomes between the two interventions for each study and we pooled the effect size using the same models. Results: Overall, 3, 536 patients were included: 1, 249 (35.3%) and 2, 287 (64.7%), undergoing sentinel node mapping and lymphadenectomy, respectively. Pooled data suggested that positive pelvic nodes were detected in 184 out of 1, 249 (14.7%) patients having sentinel node mapping and 228 out of 2, 287 (9.9%) patients having lymphadenectomy (OR:2.03; (95%CI:1.30 to 3.18);p=0.002). No difference in detection of positive nodes located in the paraaortic was observed (OR:0.93 (95%CI:0.39 to 2.18); p=0.86). Overall recurrence rate was 4.3% and 7.3% after sentinel node mapping and lymphadenectomy, respectively (OR:0.90 (95%CI:0.58 to 1.38); p=0.63). Similarly, nodal recurrences were statistically similar between groups (1.2% vs. 1.7%; OR: 1.51 (95%CI:0.70 to 3.29); p=0.29). Conclusions: In conclusion, our meta-analysis underlines that sentinel node mapping is non-inferior to standard lymphadenectomy in term of detection of paraaortic nodal involvement and recurrence rates (any site and nodal recurrence); while, focusing on the ability to detect positive pelvic nodes, sentinel node mapping could be consider superior to lymphadenectomy.